Peran Adverse Childhood Experiences terhadap Fear of Compassion pada Wanita Dewasa Awal - Widjaja, Graciella Nathania; Suryadi, Denrich (Faculty of Ushuluddin and Humanities, 2025)
Children who grow up in violent or neglectful environments may be at risk of developing Adverse Childhood Experiences. Psychological impact of ACEs is fear of compassion, or the feeling of being afraid of receiving kindness. This study aimed to examine the role of ACEs in predicting fear of compassion among early adult women using a non-experimental quantitative correlational method with 277 respondents. The instruments used were the Indonesian version of the WHO ACE-IQ (α = 0.876) and the Indonesian adapted version of the Fear of Compassion Scale (α = 0.931). The results showed a significant positive relationship between ACEs and fear of compassion (r = 0.509, p < 0.001), with a contribution of 25.9%. The mean difference test indicated no differences in ACEs or fear of compassion based on age, domicile, education, occupation, or marital status. Keywords: Adverse Childhood Experiences, Fear of Compassion, Early Adult Women. Keywords: Adverse Childhood Experiences, Fear of Compassion, Early Adult Women.